(untitled) (Italian Journal of Public Health, 2009)
The European Commission, recognizing that a number of healthcare and knowledge issues are common to all rare diseases in spite of the wide variety of their clinical manifestation, has recently initiated the promotion of national plans and comprehensive strategies for improving the provision of care to rare disease patients. In Italy, for some time, a number of coordinated initiatives have been undertaken at National and Regional level in order to provide quality care to rare disease patients. Some of these initiatives anticipate the recommendations at the European Union level. A key legal instrument has been the Ministerial Decree 279/2001 which established, with the collaboration of the Regions, the national network for the surveillance, diagnosis, treatment and cost exemption for rare diseases. Other regulations facilitate access to drugs and to assistance for the disabilities associated with rare diseases. More recently specific initiatives have been adopted to foster research on rare diseases and the involvement of patients in decision making regarding rare diseases. Another key step in the development of an effective strategy to tackle rare diseases in Italy, has been the establishment of the National Centre for Rare Diseases. The Centre is currently developing a wide variety of initiatives: some contribute to the full implementation of the national legislative provisions and to the coordination of activities among the Regions; others aim to develop autonomous initiatives within its mission of research, provision of technical expertise and documentation as well as information on rare diseases.